The Impact of Tax Incentives on Foreign Direct Investment: The Case of Tax Holiday and Corporate Income Tax Rates in Indonesia - Muhammad Ikhsan Bella; Ivan Yudianto (Journal of Accounting Auditing and Business, 2021)
This study aims to analyse the impact of tax incentives, namely tax holidays and corporate income tax rates, on Foreign Direct Investment (FDI) in Indonesia from 1981 to 2020. The sampling technique used in this study was purposive sampling so that 40 samples were obtained from 1981 until 2020 of each variable, namely FDI inflows as the dependent variable, tax holiday and corporate income tax rates as independent variables, and gross domestic product growth, inflation, and trade openness as control variables. Analysis of the data used in this study is the method of multiple regression analysis. This study consisted of two models, namely testing without control variables and with control variables. The study results without control variables show that the tax holiday positively and significantly affects FDI inflows. In contrast, the corporate income tax rate has a negative and significant effect on FDI inflows. The study results with control variables show that the tax holiday positively and significantly affects FDI inflows, income tax rates, and trade openness negatively and significantly affects FDI inflows. In contrast, Gross Domestic Product (GDP) growth and inflation have no significant effect on FDI inflows.